(3JNWjW GdMedGJ GdEYdGejI hGdEYdGfjI (B/s - (3cGaj, eUWai jhSas ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2015)
(3eGgjI GdMedI GdGYdGejI h CSSgG h CfhGYgG h CSHGH XghQgG h YhGed GdfLGM h CSHGH GdGNaGb h GdYfGUQ GdGJUGdjI ajgG h JMOjO hSGFd GdGJUGd h JfGhd GdMedGJ GdGYdGejI h JZjjQ GdGJLGgGJ h GdJNWjW GdGYdGej h eQGMd GdbjGe HGdMedI GdGYdGejI h EYOGO GdQSGdI GdGYdGejI h feGPL YfgG ceG Je GdJWQb Gdi GdGJUGdGJ GdJShjbjI h GdGYdGf h JWhQg h CgejJg h JfGhd GdeSJgdc h GdGYdGf hhcGdGJ GdGYdGf h JNWjW GdMedI GdGYdGfjI h MedI GdJNWjW (B.s
(3eQGLY U(B.281s
Keywords: (3GdEYdGe (B- (3GdEYdGf s; (3GdEYdGfs; (3GdOYGjIs